A Case of Hereditary Spherocytosis Caused by a Novel Homozygous Mutation in the SPTB Gene Misdiagnosed as β-Thalassemia Intermedia Due to a KLF1 Gene Mutation. (4th March 2019) - Yang, Kun; Ren, Quan; Wu, Yi; Zhou, Yali; Yin, Xiaolin
Abstract: We report a rare case of hereditary spherocytosis (HS) and hereditary persistence of fetal hemoglobin (Hb) (HPFH) complicated with a β-thalassemia (β-thal) trait and a Krüppel-like factor 1 ( KLF1 ) gene mutation misdiagnosed as β-thal intermedia (β-TI) due to a high percentage of Hb F. The proband presented with pale skin, jaundice and splenomegaly. Analysis of the thalassemia gene indicated β codon 17 /β A ( HBB : c.52A>T), while Hb analysis showed significantly increased Hb F levels. The proband was diagnosed to carry β-TI, and a blood transfusion regimen together with iron chelation treatment was recommended. Due to the difference between the phenotype and genotype, next generation sequencing (NGS) was performed and the proband was found to carry a homozygous mutation on the SPTB gene combined with a heterozygous mutation in KLF1 . An eosin-5-maleimide binding test (EMA-BT) showed that the mean fluorescence intensity decreased by 47.1%. The proband was finally diagnosed with HS and HPFH complicated with a β-thal trait and the high percentage of Hb F was believed to be ascribed to the KLF1 gene mutation, which is frequent in areas where thalassemia is prevalent. For patients with a β gene mutation accompanying significantly high percentage of Hb F, the diagnosis of β-TI could be warranted, and the influence of the KLF1 gene mutation should be carefully excluded to avoid misdiagnosis of other types of hereditary hemolytic diseases.